Dephasing and error dynamics affecting a singlet-triplet qubit during coherent spin shuttling - Natalie D. Foster; Jacob D. Henshaw; Martin Rudolph; Dwight R. Luhman; Ryan M. Jock (npj Quantum Information)
Abstract Quantum information transport over micron to millimeter scale distances is critical for the operation of practical quantum processors based on spin qubits. One method of achieving a long-range interaction is by coherent electron spin shuttling through an array of silicon quantum dots. In order to execute many shuttling operations with high fidelity, it is essential to understand the dynamics of qubit dephasing and relaxation during the shuttling process in order to mitigate them. However, errors arising after many repeated shuttles are not yet well documented. Here, we probe decay dynamics contributing to dephasing and relaxation of a singlet-triplet qubit during coherent spin shuttling over many N repeated shuttle operations, in a small external magnetic field B 0 ≈ 0−10 mT, and in the absence of a micromagnet. We find that losses are dominated by magnetic dephasing, most visible for small N < 103. However, incoherent spin-flip type shuttle errors become evident for large N > 103. Additionally, we estimate shuttle error rates below 10−4 out to at least N = 103, representing an encouraging figure for future implementations of spin shuttling to entangle distant qubits.